Comparative Analysis of Small Business in the Border Regions of Russia and Kazakhstan - Doroshenko, Svetlana V. (Economy of Regions, 2020)
Nowadays, comparative research in the field of small business in the border regions of Russia and Kazakhstan plays an important role, as both countries are willing to increase the relevance of this sector in the national economy. A theoretical review on the topic has demonstrated the need to intensify research focused on the development problems of the Russian- Kazakh regions, including assessments of the business sector. The study aims to comparatively assess the contribution of the border regions to the development of small business in Russia and Kazakhstan and examine the reaction of their business community to changes in the environment. I hypothesise that, in the period from 2011 to 2018, the share of the Russian and Kazakh border regions in the indicators of small business development has not changed significantly. The analysis is based on the author’s calculations of the ratio of the border regions in terms of four indicators of small business development: the number of subjects, the number of employees, turnover, and outputs. The analysis results showed that the border regions of both countries are hardly «sensitive» to government initiatives aimed at the business activity promotion. The values of the in- dicators of small business development either remain the same (as in Russia) or decrease (as in Kazakhstan). Simultaneously, the border regions of both countries demonstrate a high migration outflow that could be gradually reduced by the business sector. The significance of small business in these processes is underestimated: this economic entity organizes the flow of ma- terial, labour, and financial resources, as well as participates in socio-political processes and spatial planning in the border areas. The further research directions include comparative assessments of the development of individual entrepreneurs and medium-sized business, analysis of institutional mechanisms for small business development in the border area. Follow-up studies should also focus on developing the proposals for improving regional and municipal strategies and programmes to strengthen their border context.